Answer:
6
Step-by-step explanation:
m = 3
n = 1
Equation
m(m - n) Substitute the givens
Solution
3(3 -1 ) Evaluate what is inside the brackets.
3(2) multiply
6
Answer:
<h3>The 12th term is 1771470</h3>
Step-by-step explanation:
Since the above sequence is a geometric sequence
An nth term of a geometric sequence is given by
![A(n) = a(r)^{n - 1}](https://tex.z-dn.net/?f=A%28n%29%20%3D%20a%28r%29%5E%7Bn%20-%201%7D%20)
where a is the first term
r is the common ratio
n is the number of terms
From the question
a = 10
To find the common ratio divide the previous term by the next term
That's
r = 30/10 = 3 or 90/30 = 3 or 270/90 = 3
Since we are finding the 12th term
n = 12
So the 12th term is
![A(12) = 10( {3})^{12 - 1}](https://tex.z-dn.net/?f=A%2812%29%20%3D%2010%28%20%7B3%7D%29%5E%7B12%20-%201%7D%20)
![A(12) = 10 ({3})^{11}](https://tex.z-dn.net/?f=A%2812%29%20%3D%2010%20%28%7B3%7D%29%5E%7B11%7D%20)
<h3>A(12) = 1771470</h3>
Hope this helps you
Answer:
8 3/5
false
Step-by-step explanation:
8 x2 is 16; we have a negative sign, so that makes our answer -16
Answer:
20
Step-by-step explanation:
1 hour=2 kg
10 hrs=10×2=20
Mark as brainliest please!